A reading of Edward Taylor - Davis, Thomas M. (Univ. of Delaware Press u.a., 1992)
A Reading of Edward Taylor is a study of Taylor's poetry in the sense that Thomas M. Davis is interested in how the nature of the poems evolves during the nearly fifty years Taylor served as minister in Westfield, Massachusetts. The first part of the book examines the long doctrinal poem, Gods Determinations, as the poem in which Taylor emerges as an accomplished poet. The final section of the poem, the "Choral Epilogue," with its emphasis on praising God in song, leads directly to the initial poems of the Preparatory Meditations, the more than two hundred meditative poems that Taylor wrote over the next forty years. The early poems in Series 1 exhibit only loosely organized sequences; some are directly prompted by the Lord's Supper, but many are related in only indirect ways to the Sacrament. These poems, in their range and celebration of the joys of grace, are some of Taylor's best
Keywords: Taylor, Edward <1642-1729> -- Criticism and interpretation; Taylor, Edward -- 1642-1729; Christelijke literatuur; Gedichten; Lyrik; Christian poetry, American -- History and criticism